Preparation and Mechanical Properties of Cemented Uranium Tailing Backfill Based on Alkali-Activated Slag - Fulin Wang; Guoliang Chen; Lu Ji; Zhengping Yuan (Advances in Materials Science and Engineering)
Backfilling disposal based on cement solidification is one of the ways to solve the environmental and safe problems of uranium tailing surface stacking. Alkali-activated slag, especially sodium silicate activated geopolymer, has become the preferred cementing material for the uranium tailing backfilling system because of its advantages of corrosion resistance and high strength. In this paper, uranium tailings and slag are taken as research objects, and the unconfined compressive strength (UCS) is taken as the main quality index. The preparation method of the cemented uranium tailing backfill based on alkali-activated slag was studied, hereinafter referred to as CUTB. The effects of additive amount, activator amount and activator modulus on the strength of CUTB were investigated. The results show that alkali-activated slag is an effective cementing material for the backfilling system of uranium tailing aggregate. The maximum UCS of 28 d age in the test groups is 16.45 MPa. Quicklime is an important additive for preparing CUTB. When the amount of quicklime is 0%, the early and late strengths of the filling body cannot be measured or at a very low level. At the age of 7 d, the order of each factor is additive amount > activator modulus > activator amount, but at the age of 28 d, the order of each factor is additive amount > activator amount > activator modulus. The test results can provide a basis for choosing cementitious materials for backfilling disposal of uranium tailings.